Expression analysis of hormonal pathways and defense associated genes in gamma-rays mutagenized wheat genotypes against combined stresses of spot blotch and terminal heat - Singh, G. Mahendra; SrinathaReddy S; Sharma, Gaurav; Bakshi, Suman; Kumar, Uttam; Bhati, Pradeep; Jambhulkar, Sanjay J.; Chand, Ramesh; Joshi, Arun Kumar; Vinod Kumar Mishra; Sandeep Sharma (Elsevier, 2022)
Wheat (Tritium aestivum L.) productivity is severely hampered by various pathogens and changing climatic conditions. Spot blotch and terminal heat stress are the major constraints of wheat production in the eastern Gangetic plains of India. To identify novel breeding sources and to understand underlying resistance mechanisms, forty-four gamma rays mutagenized wheat genotypes, derived from three different parents were screened under favourable agro-ecological conditions for spot blotch and terminal heat stress. Ten mutants showed reduced spot blotch infection calculated based on Area Under Disease Progress Curve (AUDPC), than their respective parents. The mutant TAW41 had the least infection (AUDPC: 354.32), significantly lower than its parent HD2967 (AUDPC: 675.51) and other checks. TAW41 also had a higher Normalized Difference Vegetation Index (NDVI) and chlorophyll content than the parent. Gene expression analysis of TAW41 showed differential accumulation of transcripts involved in hormonal pathways (Salicylic acid, Jasmonic acid, and ethylene) and other defense-associated genes, indicating that TAW41 might have unique resistance mechanism that facilitates this genotype to perform better against the combined stress of spot blotch and terminal heat. Hence, mutant TAW41 has been identified as a novel source of resistance that could be exploited in wheat improvement programmes to enhance tolerance to spot blotch and terminal heat stress.